Endovascular repair of pseudoaneurysms after open surgery for aortic coarctation - Kotelis, Drosos; Bischoff, Moritz; Rengier, Fabian; Ruhparwar, Arjang; Gorenflo, Matthias; Böckler, Dittmar (Interactive cardiovascular and thoracic surgery, 2016)
To analyse early and long-term results of thoracic endovascular aortic repair (TEVAR) in patients with pseudoaneurysms after open aortic coarctation (CoA) repair.